Influence of Competence and Supervision on the Management of the Village Financial System (Siskeudes) in Nganjuk Regency - Rahayu, Dwi Puji; Ambarwati, Ambarwati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine the effect of human resources consisting of competence, and supervision on the management of village financial system application in villages in Nganjuk district. The research method used is a quantitative research method with primary data obtained from questionnaire data which is measured with a likertscale.The population in this study were all villages in Nganjuk district as many as 264 villages, with the respondents being the siskuedes operator, Village secretary and village treasure, while the sample uses the slovin formula, resulting 73 samples.The research data was processed using the classical assumption test consisting of the Normality Test, Multicollinerity Test and Multiple Linear Regression Test. The results of this study conclude that 1) Competence has a positive and significant effect on the management of village finsncialsysten applications in Nganjuk district 2). Supervision has a positive and significant effect on the management of village financial system applications in Nganjuk district.3). Competence and supervision together effect the management of village financial system applications in Nganjuk district.